Regulation of cartilage cell fate determination and homeostasis. - Cairns, Dana. (2017)
Abstract: We first studied the role of Shh in patterning the somite during early embryonic development. We found that differing levels of Shh signaling elicit differing responses from somitic cells: the lowest level of Shh signaling allows dermomyotomal gene expression, intermediate levels induce loss of dermomyotomal markers and activation of myogenic differentiation, and higher levels induce loss of myotomal markers and activation of sclerotomal gene expression. We also found that under high levels of Wnt signaling, Shh signals act to maintain the expression of dermomyotomal and myotomal markers. One sclerotomal gene induced by high Shh signaling is Nkx3.2. Forced expression of Nkx3.2 blocks expression of dermomyotomal marker Pax3 both in vitro and in vivo. Conversely, expression of Pax3 in somites can block Shh-mediated induction of sclerotomal gene expression. In summary, Pax3 and Nkx3.2 set up mutually repressing somitic cell fates.. Muscle is a tissue located in close proximity to cartilage tissue. We found that chondrocytes cultured with C2C12 muscle cells exhibited increased production of cartilage matrix proteins. Furthermore, muscle cell-conditioned medium led to increased cartilage matrix production, suggesting that muscle cells secrete pro-chondrogenic factors. Furthermore, we showed that muscle cells diminish the response of chondrocytes to arthritis-associated pro-inflammatory cytokines IL-1-beta and TNF-alpha. We found that chondrocytes cocultured with muscle cells or cultured in muscle cell-conditioned medium significantly enhanced the expression of cartilage matrix proteins (collagen II and collagen IX) by interfering with IL-1-beta and TNF-alpha downstream signaling mediators (including NFkappaB, ESE-1, Cox-2, and GADD45beta), and causing the attenuated expression of cartilage-degrading enzymes (MMPs and ADAMTS4). This result may ultimately lead to the discovery of novel factors that regulate cartilage formation and homeostasis, and provide insights into improving the strategies for regenerating cartilage. Lastly we describe a mechanism by which we investigate the mechanism by which these muscle progenitor cells adopt a cartilage fate. We show that chick muscle satellite cells can be converted to express cartilage matrix proteins in vitro when cultured in chondrogenic medium containing TGF-beta or BMP2. Ectopic expression of the myogenic factor Pax3 prevents chondrogenesis in these cells, while chondrogenic factors Nkx3.2 and Sox9 promote this cell fate transition. We found that Nkx3.2 and Sox9 repress the activity of the Pax3 promoter. A reverse function mutant of Nkx3.2 blocks the ability of Sox9 to both inhibit myogenesis and induce chondrogenesis, suggesting that Nkx3.2 is required for Sox9 to promote chondrogenesis. Finally, in an in vivo mouse model of fracture healing using lineage-traced muscle progenitor cells, Nkx3.2 and Sox9 are significantly upregulated while Pax3 is significantly downregulated in the muscle progenitor cells that give rise to chondrocytes during fracture repair.; Thesis (Ph.D.)--Tufts University, 2012.; Submitted to the Dept. of Cell, Molecular & Developmental Biology.; Advisor: Li Zeng.; Committee: Gordon Huggins, John Castellot, Thomas Linsenmayer, and Louis Gerstenfeld.; Keyword: Cellular biology.